The results of electrophysiological study and radio-frequency catheter ablation in pediatric patients with tachyarrhythmia - Celiker, Alpay; Kafali, Gülden; Karagöz, Tevfik; Ceviz, Naci; Ozer, Sema (The Turkish Journal of Pediatrics, 2003)
A total of 135 consecutive pediatric patients (pts) with tachyarrhythmia ranging from two to 21 years of age (median age 11 years) underwent electrophysiological study (EPS) between January 1994 and July 2001. Tachycardia could not be induced in 38 of 135 pts (28%) and studies in these patients were accepted as the normal EPS. Supraventricular tachyarrhythmia mechanisms were atrioventricular (AV) accessory pathways in 47 patients (manifest accessory pathways in 23 patients, concealed accessory pathways in 17 patients, permanent junctional reciprocating tachycardia in 7 patients), re-entry without accessory pathway in 26 patients (AV nodal reentry tachycardia in 20 patients, atrial flutter in 5 patients, sinus node re-entry tachycardia in 1 patient) and atrial ectopic tachycardia in eight patients. The diagnosis of ventricular tachycardia (VT) was made in 16 patients. Seventy-three of the 97 patients with the diagnosis of tachyarrhythmia as a result of EPS underwent radiofrequency (RF) catheter ablation. The indications, early results, complications, safety and efficacy of RF catheter ablation were reviewed in these patients. Among the 73 patients who underwent RF ablation (85 procedures), the overall final success rate for all the diagnoses was 82% (60 of 73 patients). The median follow-up period for all patients was 16 months (range 2 to 60 months). Total recurrence rate in 73 patients was 4% (3 patients). Re-ablation was performed in only one of them and was successful. Procedure-related complications occurred in eight patients (11%): transient third-degree AV block in one patient, transient second-degree AV block in one patient, atrial flutter in two patients (1 needed direct current cardioversion), and atrial fibrillation in three patients (2 needed defibrillation and transient pacemaker implantation). In one patient with permanent third-degree AV block a transvenous pacemaker implantation was required. These midterm results suggest that RF catheter ablation has a good success rate and a low complication rate in pediatric patients, especially when it is carried out in experienced pediatric cardiology centers.